The association of CXCR4 expression with prognosis and clinicopathological indicators in colorectal carcinoma patients: a meta‐analysis. Issue 5 (15th January 2014) - Lv, Shunzeng; Yang, Yakun; Kwon, Sera; Han, Mingzhi; Zhao, Fangfang; Kang, Huihui; Dai, Congxin; Wang, Renzhi
<x xml:space="preserve">Abstract</x> Aims The clinical relevance of expression of chemokine receptor 4 (CXCR4) in colorectal carcinoma (CRC) remains controversial; our aim was to identify the precise relationship of CXCR4 to prognosis and clinicopathological features. Methods and results A meta‐analysis was performed. Original data included the hazard ratios (HRs) of recurrence‐free survival (RFS), overall survival (OS) and odds ratio (OR) in CRC patients. We pooled HR/OR with 95% confidence intervals (CIs) to estimate the hazard. A total of 20 published studies (including 2253 patients) were eligible. RFS and OS were related significantly to CXCR4 expression, with HRs 1.62 (95% CI 1.24–2.11; P < 0.0001) and 1.68 (95% CI 1.31–2.14; P < 0.0001), respectively. In addition, a significant association was revealed between positive CXCR4 expression and age (less than median age: OR 0.78, 95% CI 0.62–0.98; P = 0.03), stage (I and II: OR 0.46, 95% CI 0.32–0.66; P < 0.0001), grade (well/moderately differentiated: OR 0.74, 95% CI 0.56–0.98; P = 0.04), location (colon: OR: 0.73, 95% CI 0.57–0.95; P = 0.02), lymph node invasion (present: OR2.14, 95% CI 1.36–3.37; P = 0.001), and distant metastasis (present: OR 2.40; 95% CI 1.36–4.23; P = 0.003). Heterogeneity was observed among the included studies with regard to stage (I2 = 58 %), lymph node invasiveness (I2 = 74%) and distant metastasis (I2 = 56%). No publication bias was observed. Conclusions Chemokine receptor 4 expression indicates poorer prognosis in older patients and advanced stage or poor differentiation in CRC, and also serves as an indicator of lymph node and distal organ metastasis. Surprisingly, high CXCR4 expression may indicate that the location of the tumour is the rectum. Thus, CXCR4 could help to predict outcome and guide clinical therapy.